Characterizing shallow groundwater in hillslope aquifers using isotopic signatures: a case study in the Upper Blue Nile Basin, Ethiopia - Setargie, T. A.; Tilahun, Seifu A.; Schmitter, Petra S.; Moges, M. A.; Gurmessa, S.K.; Tsunekawa, A.; Tsubo, M.; Berihun, Mulatu L.; Fenta, A. A.; Haregeweyn, Nigussie (Elsevier, 2021)
Study region: Robit-Bata watershed, Upper Blue Nile basin, Ethiopia. Study focus: Stable isotopes of water (Oxygen-18 and Deuterium) were used as tracers to estimate the contribution of groundwater in shallow hillslope aquifers to streamflow in the Robit-Bata watershed. To assess the spatiotemporal variability of shallow groundwater and develop a hydrograph separation technique, we collected rainfall, shallow groundwater, and streamflow samples and analyzed their d18O and d2 H isotopic compositions. The local meteoric water line (LMWL) and local evaporative line (LEL) of the study area were determined and compared with the global meteoric water line (GMWL). A standard unweighted two-component isotope-based hydrograph separation model was used to determine the percentage contribution of shallow groundwater to streamflow. New hydrological insights for the region: The LMWL (d2 H = 8.63·d18O + 18.2) mostly showed heavy isotopic enrichment relative to GMWL, and the LEL (d2 H = 5.45·d18O + 6.96) indicated isotopic enrichment compared to Ethiopian lakes. Shallow groundwater responded rapidly to rainfall, with good spatial correlation depending on topographic positions of wells. Pre-event water contributed 90% when the watershed reached maximum storage. This finding gives insight towards the predominant runoff generation process and has significant implications for sustainable dry season irrigation expansion in the area as the sub-surface flow drains out of the watershed from October onwards reducing water tables in the shallow wells.